2012
DOI: 10.6106/jcepm.2012.2.4.011
|View full text |Cite
|
Sign up to set email alerts
|

A Construction Supply Chain Management Process with RFID/WSN-based Logistics Equipment

Abstract: Construction supply chain management (CSCM) has become one of the critical factors that determine the success of a construction project as it becomes increasingly complicated and mega-sized. Particularly for high-rise or mega-sized building construction, just-in-time supply chain management is required due to lack of storage space and effective logistics for construction components and materials at a construction site. Despite the fact that research and development of radio frequency identification (RFID) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…They showed that material, labor and information flows significantly affect project's performance. In order to overcome the difficulty in coordinating the large number of divers material supplies, many research efforts focuse on testing of state-of-the-art IT in enterprise resource planning [2], supply chain logistics [3] and material management at field level [4].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that material, labor and information flows significantly affect project's performance. In order to overcome the difficulty in coordinating the large number of divers material supplies, many research efforts focuse on testing of state-of-the-art IT in enterprise resource planning [2], supply chain logistics [3] and material management at field level [4].…”
Section: Introductionmentioning
confidence: 99%
“…The article [22] showed the importance of construction supply chain management (CSCM) and how its is helpful. Construction projects are complex and big in size, e.g., high rised buildings or mega-sized buildings.…”
Section: Wireless Communication Technologiesmentioning
confidence: 99%
“…Previous studies [13]- [15] addressed these two flows by merging information and logistics. The research studies also showed that with the help of technology transference [16]- [18] and new technologies integration e.g., RFID [19], robotics [20], [21], WiFi and communication technologies [22]- [25] etc., the process of logistics and transportation has become more flexible. The objective of this paper is to pinpoint the advantages of existing technologies and importance of VANET technology in logistics and transportation with respect to the previously mentioned issues, and to discuss use of multiple technologies together to a get solution for complex processes.…”
Section: Fig 1: Intelligent Transport System (Its) and Underlying Tementioning
confidence: 99%